Resilience in agro-ecological landscapes: process principles and outcome indicators - Fabricius, C.; Novellie, P.; Ringler, Claudia; Uhlenbrook, Stefan; Wright, D. (International Water Management Institute, 2021)
This paper explores outcome indicators and process principles to evaluate landscape resilience in agro-ecosystems, drawing on outcome indicator case studies of the CGIAR Research Program on Water, Land and Ecosystems (WLE). Four questions are addressed: (1) which outcome indicators and process principles feature most prominently in the seminal literature on resilient agro-ecological landscapes? (2) to what extent are these principles represented in CGIAR Outcome Impact Case Reports (OICRs) and selected peer-reviewed studies? (3) how does the use of process principles in the case studies compare to their occurrence in the theoretical literature? and (4) which process principles co-occur with related outcome indicators in the OICRs? The findings enable researchers and practitioners to be more specific about the outcomes and processes that drive resilience in agro-ecosystems, thereby informing adaptive program management. Seven novel research themes are proposed.